Design and fabrication of a portable low-cost rice milling machine with automatic feeding mechanism - Hasan Farid Khan,; Shehroze Khan,; Ali Akbar,; Rizwan Ahmad,; Moazzam Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Rice is an important source of food for humans and holds higher importance, it grows on plants in a shell called a hull. To extract, the rice from its shells a rice milling machine is used. These processing machines are costly and not feasible for farmers to buy for their domestic purposes or for small-scale industries. For overcoming this problem an innovative and affordable rice mill is required, for small businesses. Not only the cost but also the machine parameters are much important. This paper is aimed to evaluate the performance of the designed small-sized model of the rice milling machine along with the analysis of the set parameters for the economic rice extraction from the hull without damaging the kernels. In the first step, a conceptual model in CAD was drawn including detailed specifications. In the second step, the design was evaluated and utilized to reproduce/ fabricate each component for a practical machine. Lastly, the machine was evaluated for its performance. Moreover, an automatic feeding system was also introduced as an innovation to reduce feeding labor and increase production. From the results, it was found that the automatic feeding system was reliable, moreover, the 3-horsepower motor was reduced to 2 horsepower for power saving. The cost of the machine was reduced from 80000Pkr to 55000Pkr. However, the rice processing speed was reduced to 100 kg/hour, from 200 kg/hour, which is aimed to be compensated via an automatic feeding mechanism.